2016
DOI: 10.3791/54972
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-derived Method to Transport Genes and Proteins Across Cellular and Organellar Barriers in Plants

Abstract: The capacity to introduce exogenous proteins and express (or down-regulate) specific genes in plants provides a powerful tool for fundamental research as well as new applications in the field of plant biotechnology. Viable methods that currently exist for protein or gene transfer into plant cells, namely Agrobacterium and microprojectile bombardment, have disadvantages of low transformation frequency, limited host range, or a high cost of equipment and microcarriers. The following protocol outlines a simple an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Nanomaterial-mediated nonviral intracellular delivery has enabled numerous advances in animal research and for diverse biomedical applications. , However, due to the significant structural differences between mammalian cells and mature plant cells, these nanodelivery systems are not often directly translatable to plants. Recent work has shown that certain nanomaterials can serve as carriers to deliver plasmid DNA and RNA into intact plant cells and protoplasts. Mitter et al applied clay nanosheets to deliver pathogen-specific double-stranded RNA to intact leaves for crop protection against plant viruses with great success . Other studies have shown that single-walled carbon nanotubes can mediate plasmid DNA delivery and transient protein expression in mature plant leaves and have also enabled highly efficient siRNA delivery and gene silencing in intact plants. , Moreover, DNA nanostructures with certain mechanical properties were able to enter cells for efficacious siRNA delivery in mature plants. , Conversely, other nanomaterials that are ubiquitously used for delivery in animal systems such as gold nanoparticles and lipid vesicles have not yet been reported to enable biomolecule delivery in plants, which could be due in part to the plant cell wall excluding the entry of abiotic particles above the small plant cell wall size exclusion limit of ∼5–20 nm. , …”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterial-mediated nonviral intracellular delivery has enabled numerous advances in animal research and for diverse biomedical applications. , However, due to the significant structural differences between mammalian cells and mature plant cells, these nanodelivery systems are not often directly translatable to plants. Recent work has shown that certain nanomaterials can serve as carriers to deliver plasmid DNA and RNA into intact plant cells and protoplasts. Mitter et al applied clay nanosheets to deliver pathogen-specific double-stranded RNA to intact leaves for crop protection against plant viruses with great success . Other studies have shown that single-walled carbon nanotubes can mediate plasmid DNA delivery and transient protein expression in mature plant leaves and have also enabled highly efficient siRNA delivery and gene silencing in intact plants. , Moreover, DNA nanostructures with certain mechanical properties were able to enter cells for efficacious siRNA delivery in mature plants. , Conversely, other nanomaterials that are ubiquitously used for delivery in animal systems such as gold nanoparticles and lipid vesicles have not yet been reported to enable biomolecule delivery in plants, which could be due in part to the plant cell wall excluding the entry of abiotic particles above the small plant cell wall size exclusion limit of ∼5–20 nm. , …”
Section: Introductionmentioning
confidence: 99%
“…We formulated a PICsome by mixing two peptidestwo-armed and carboxylated oligolysinesprepared by chemoenzymatic polymerization followed by chemical modification (Figure ). To enhance their availability as a protein transduction system in plants, we cross-linked the PICsome (hereinafter called CL-PICsome), and to increase their protein transduction efficiency in plants, we modified their surface with a CPP (hereinafter called CPP-PICsome) via click chemistry using copper­(I)-catalyzed azide–alkyne cycloaddition . We used azide-terminated KAibA-N 3 peptides (amino acid sequence KUAKUAKUA, where U refers to α-aminoisobutyric acid, Aib) as the CPP because they show excellent cell-penetrating capacity in both mammalian and plant cells because of their ability to stabilize helical structures and improve resistance to enzymatic degradation. , Dynamic light scattering (DLS) measurements showed that PICsomes prepared at a KAibA peptide concentration of 500 μM had a hydrodynamic diameter of 169 ± 9 nm (Table S1).…”
mentioning
confidence: 99%
“…113,114 This peptide was able to complex pDNA and when combined with a CPP, delivery and expression of a pDNA containing a GFP reporter construct could be observed within the mitochondria of A. thaliana leaves upon infiltration. 115 Follow-up studies using this peptide showed that the delivered pDNA was also capable of integration into the mitochondrial genome and a reporter GFP construct could be actively translated upon integration. 112 Furthermore, the use of carbon nanotubes functionalized with the same mitochondrial targeting and DNA binding sequences showed that delivery efficiencies could be enhanced almost 30-fold compared with the peptide only approaches as demonstrated in a recent study by Law et al 56 (Fig.…”
Section: Mitochondria-targeted Gene Deliverymentioning
confidence: 99%